Induction of pulmonary fibrosis by cerium oxide nanoparticles - Ma, Jane Y. (Toxicol Appl Pharmacol, 2012)
Cerium compounds have been used as a diesel engine catalyst to lower the mass of diesel exhaust particles, but are emitted as cerium oxide (CeO(2)) nanoparticles in the diesel exhaust. In a previous study, we have demonstrated a wide range of CeO(2)-induced lung responses including sustained pulmonary inflammation and cellular signaling that could lead to pulmonary fibrosis. In this study, we investigated the fibrogenic responses induced by CeO(2) in a rat model at various time points up to 84 days post-exposure. Male Sprague Dawley rats were exposed to CeO(2) by a single intratracheal instillation. Alveolar macrophages (AM) were isolated by bronchial alveolar lavage (BAL). AM-mediated cellular responses, osteopontin (OPN) and transform growth factor (TGF)-β1 in the fibrotic process were investigated. The results showed that CeO(2) exposure significantly increased fibrotic cytokine TGF-β1 and OPN production by AM above controls. The collagen degradation enzymes, matrix metalloproteinase (MMP)-2 and -9 and the tissue inhibitor of MMP were markedly increased in the BAL fluid at 1 day- and subsequently declined at 28 days after exposure, but remained much higher than the controls. CeO(2) induced elevated phospholipids in BAL fluid and increased hydroxyproline content in lung tissue in a dose- and time-dependent manner. Immunohistochemical analysis showed MMP-2, MMP-9 and MMP-10 expressions in fibrotic regions. Morphological analysis noted increased collagen fibers in the lungs exposed to a single dose of 3.5 mg/kg CeO(2) and euthanized at 28 days post-exposure. Collectively, our studies show that CeO(2) induced fibrotic lung injury in rats, suggesting it may cause potential health effects.